Structural elucidation of a novel arabinogalactan LFP-80-W1 from Lycii fructus with potential immunostimulatory activity - Liang, Xiaofei; Liu, Mengqiu; Guo, Sheng; Zhang, Fang; Cui, Wanchen; Zeng, Fei; Xu, Mingming; Qian, Dawei; Duan, Jinao (Frontiers in Nutrition, 2023)
Polysaccharides are the most important effective components of Lycii fructus, which has a variety of biological activities and broad application prospects in the fields of medicine and food. In this study, we reported a novel arabinogalactan LFP-80-W1 with potential immunostimulatory activity. LFP-80-W1 was a continuous symmetrical single-peak with an average molecular weight of 4.58 × 104 Da and was mainly composed of arabinose and galactose. Oligosaccharide sequencing analyses and NMR data showed that the LFP-80-W1 domain consists of a repeated 1,6-linked β-Galp main chain with branches arabinoglycan and arabinogalactan at position C-3. Importantly, we found that LFP-80-W1 could activate the MAPK pathway and promote the release of NO, IL-6, and TNF-α cytokines in vitro. Therefore, our findings suggest that the homogeneous arabinogalactan from Lycii fructus, can be used as a natural immunomodulator.